Theoretical Evaluation on The Interaction Between Triglycerides and Methylxanthines Using Density Functional Theory B3LYP/6-31G(d,p) and Molecular Electrostatic Potential - Azmi, N.F.M.; Ali, R.; Azmi, A.A.; Rozaini, M.Z.H.; Bulat, K.H.K.; Anuar, S.T. (Asian Journal of Chemistry, 2020)
The binding, interaction and distortion energies between the main triglycerides, palmitic-oleic-stearic (POS) in cocoa butter versus palmitic-oleic-palmitic (POP) in refined, bleached and deodorized (RBD) palm oil with cocoa′s methylxanthines (caffeine, theobromine, and theophylline) during the production of chocolate were theoretically studied and reported. The quantum mechanical software package of Gaussian09 at the theoretical level of density functional theory B3LYP/6-31G(d,p) was employed for all calculations, optimization, and basis set superposition errors (BSSE). Geometry optimizations were carried out to the minimum potential energy of individual species and binary complexes formed between the triglycerides, methylxanthines and polyphenols. The interaction energies for the optimized complexes were then corrected for the BSSE using the counterpoise method of Boys and Bernardi. The results revealed that the binding energy and interaction energy between methylxanthine components in cocoa powder with triglycerides were almost of the same magnitude (13.6-14.5 and 3.4-3.7 kJ/mol, respectively), except for the binary complex of POS-caffeine (25.1 and 10.7 kJ/mol, respectively). Based on the molecular geometry results, the hydrogen bond length and angle correlated well with the interaction energies. Meanwhile, the POS-caffeine complex with two higher and almost linear bond angles showed higher binding and interaction energies as compared to the other methylxanthines. Therefore, a donor-acceptor analysis showed that the hydrogen bond strength was proven using the molecular electrostatic potential (MEP), which resulted in parallel outcomes. The research results were believed to be one of the factors that contributed to the rheological behaviour and sensory perception of cocoa products, especially chocolate.